The Role of Optical Coherence Tomography (OCT) in Glaucoma: Emphasis on Cirrus HD-OCT - Nugraha, Andarisa Rachman; Komaratih, Evelyn (Vision Science and Eye Health Journal, 2025)
Introduction: Glaucoma is a rapidly growing illness affecting the population, and is the leading cause of irreversible blindness across the world. Losing vision can occur without any warning, which is why the disorder must be managed as soon as it is diagnosed. Glaucoma is diagnosed and managed using several optical tests, and Cirrus high-definition optical coherence tomography (HD-OCT) is among the most important. Purpose: Glaucoma is commonly diagnosed or monitored by changes in the RNFL. This review will explore changes in glaucomatous structures as detected by Cirrus HD-OCT. Structural elements such as the ganglion cell layer (GCL), inner plexiform layer (IPL), and the optic nerve head (ONH) will be the primary focus. Reviews: Glaucoma relies heavily on the Cirrus HD-OCT for detecting RNFL and GCL changes, which can occur five years or more before visual field changes that can threaten vision. The GCL/IPL layers, especially in preperimetric glaucoma, do provide an incredibly high sensitivity for detecting glaucomatous changes. The guided progression analysis (GPA) was developed to allow Cirrus HD-OCT to track disease progression over time without the identified 'normative databases'. Nevertheless, caution is needed when interpreting GCL/IPL changes in older individuals with macular degeneration. Conclusions: Cirrus HD-OCT is essential for early detection and glaucoma monitoring, offering valuable insights into structural changes in the RNFL, GCL/IPL, and ONH. The use of GPA enhances disease progression monitoring. Future research should focus on artificial intelligence and the creation of localized normative databases to further optimize glaucoma diagnosis and patient care.